Design and manufacturing of casting molds for the housing of a hand-operated seed grinding machine - Wealth Nwauzi, Chinwendu; Bodzás, Sándor (Journal of Production Engineering, 2025)
This study investigates the design and manufacturing of casting molds for the housing of a hand-operated seed grinding machine, aimed at delivering cost-effective and durable solutions for rural applications. The study began with comprehensive CAD modelling of the housing, segmented into five parts: inlet funnel, cylindrical chamber, vertical support bracket, reinforcement gusset, and mounting base. Mold geometry was optimized for cope and drag design, incorporating considerations such as parting lines, draft angles, cooling channels, gate area, clamping force, and shrinkage to minimize casting defects. CNC milling and EDM were employed to machine tool steel (H13/P20) molds with high precision (±0.01–0.05 mm) and fine surface finishes (Ra 0.1–0.2 μm). Post-processing included heat treatment (~50 HRC) and polishing. Stainless steel 304 was chosen for the final part due to its corrosion resistance. Dimensional accuracy and surface integrity were verified using CMM and profilometry. Trial casting of the inlet funnel confirmed mold functionality. FEA was performed on the AISI 304 housing under fixed-base boundary conditions, internal pressure (12,000 N/m²), a 1000 N vertical load, and gravity. Results showed low stress (24.75 MPa), minimal displacement (0.0633 mm), and a high safety factor (8.35), confirming structural soundness. The optimized mold design enhances part quality and production efficiency, supporting sustainable, low-cost manufacturing of agricultural components.